The Association Between Chemoradiation-related Lymphopenia and Clinical Outcomes in Patients With Locally Advanced Pancreatic Adenocarcinoma. (June 2015) - Wild, Aaron T.; Ye, Xiaobu; Ellsworth, Susannah G.; Smith, Jessica A.; Narang, Amol K.; Garg, Tanu; Campian, Jian; Laheru, Daniel A.; Zheng, Lei; Wolfgang, Christopher L.; Tran, Phuoc T.; Grossman, Stuart A.; et al.
Abstract : Objectives: Lymphopenia is a common consequence of chemoradiation therapy yet is seldom addressed clinically. This study was conducted to determine if patients with locally advanced pancreatic cancer (LAPC) treated with definitive chemoradiation develop significant lymphopenia and if this affects clinical outcomes. Methods: A retrospective analysis of patients with LAPC treated with chemoradiation at a single institution from 1997 to 2011 was performed. Total lymphocyte counts (TLCs) were recorded at baseline and then monthly during and after chemoradiation. The correlation between treatment-induced lymphopenia, established prognostic factors, and overall survival was analyzed using univariate Cox regression analysis. Important factors identified by univariate analysis were selected as covariates to construct a multivariate proportional hazards model for survival. Results: A total of 101 patients met eligibility criteria. TLCs were normal in 86% before chemoradiation. The mean reduction in TLC per patient was 50.6% (SD, 40.6%) 2 months after starting chemoradiation ( P <0.00001), and 46% had TLC<500 cells/mm 3 . Patients with TLC<500 cells/mm 3 2 months after starting chemoradiation had inferior median survival (8.7 vs. 13.3 mo, P =0.03) and PFS (4.9 vs. 9.0 mo, P =0.15). Multivariate analysis revealed TLC<500 cells/mm 3 to be an independent predictor of inferior survival (HR=2.879, P =0.001) along with baseline serum albumin (HR=3.584, P =0.0002), BUN (HR=1.060, P =0.02), platelet count (HR=1.004, P =0.005), and radiation planning target volume (HR=1.003, P =0.0006). Conclusions: Severe treatment-related lymphopenia occurs frequently after chemoradiation for LAPC and is an independent predictor of inferior survival.